Facile synthesis of Al/Fe bimetallic (oxyhydr)oxide-coated magnetite for efficient removal of fluoride from water. Issue 20 (5th September 2020) - Fu, Haoyang; He, Hongfei; Usman, Muhammad; Chen, Qingze; Laipan, Minwang; Yang, Yixuan; Zhu, Runliang; Cai, Limei
ABSTRACT: In this work, we developed a novel magnetic bimetallic Al/Fe (oxyhydr)oxide adsorbent through a facile and cost-effective method and explored its potential to adsorb fluoride in water. Its synthesis involved corrosion of natural magnetite in aluminium chloride solution, followed by titration with NaOH solution for in-situ synthesis of Al/Fe (oxyhydr)oxide-coated magnetite (Mag@Al2 Fe). Characterization data indicated a uniform coating of Al/Fe (oxyhydr)oxide on magnetite, and the resulting composite possessed large specific surface area (∼90 m 2 /g) and good magnetic property. In batch adsorption experiments, the isotherm and kinetic data fitted well to the Langmuir model and pseudo-second-order model, respectively. The maximum adsorption capacity of Mag@Al2 Fe is 26.5 mg/g, which was much higher than natural magnetite (0.44 mg/g). Moreover, this material retained high adsorption capacity toward fluoride within a wide pH range (3.0–8.0) and offered facile magnetic separation from water. Influence of competing ions was also evaluated which showed that the presence of Cl − and NO3 − posed negligible interference, while HCO3 − and SO4 2− had negative effects on fluoride adsorption. Thermodynamic investigations revealed that fluoride adsorption was exothermic and spontaneous. The observed increase in solution pH and formation of Al–F and Fe–F bonds (as indicated by XPS analysis) after fluoride adsorption suggested the major adsorption mechanism of ligand exchange. Besides, the adsorption/desorption cycle studies demonstrated the well-retained performance of Mag@Al2 Fe for repeated application after regeneration by 0.5 mol/L NaOH solution. Facile synthesis, high defluoridation, lower cost, and quick separation of Mag@Al2 Fe indicates its promising potential for drinking water defluoridation. GRAPHICAL ABSTRACT: